The Existence Of Gold Prices As A Mediating Factor In Banking Sector Profits - Sari, Novi Primita; Sangadah, Dhurotus (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2024)
The main activities carried out by banks aim to increase equitable distribution of economic growth and maintain national stability towards increasing prosperity. Strict regulations in the banking industry require the banking industry to improve its performance, including in the aspect of achieving profits. Achieving this profit can be improved by analyzing the factors that shape profilability. The aim of the research is to find out how the role of the amount of deposits and credit mediates the influence of gold prices on return on assets. The results of this research show that individual testing to determine the determinants of savings shows that prices have a positive and significant influence while the determinants of credit, savings have a significant positive influence. Factors forming return on assets, savings and credit, have a significant positive influence on return on assets, while the price of gold has a significant negative influence. In the analysis test, the savings channel variable was able to mediate (parcel mediation) the effect of gold prices on return on assets as well as credit also showed its ability to mediate (parcel mediation) the effect of savings on return on assets. However, if you look at the VAF value, the credit variable has a better level of mediation compared to savings, so that for state-owned banks to increase return on assets it will be easier if they channel savings in the form of credit.